2010
DOI: 10.1016/j.spa.2010.02.004
|View full text |Cite
|
Sign up to set email alerts
|

The Föllmer–Schweizer decomposition: Comparison and description

Abstract: This paper proposes two main contributions concerning the Föllmer-Schweizer decomposition (called hereafter the FS-decomposition). First we completely elaborate the relationship between this decomposition and the Galtchouk-Kunita-Watanabe decomposition under the minimal martingale measure. The difference between these two decompositions is highlighted in a very practical example, and the martingale tools that enhance this difference are illustrated in the semimartingale framework as well. The second main contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 26 publications
0
24
0
1
Order By: Relevance
“…The existence of the FS-decomposition has been studied by many authors, see, e.g., [17] and [18]. In particular, it was shown that the decomposition exists in the case of exponential Lévy models.…”
Section: Hedging In the Exponential Lévy Setting: The Semimartingale mentioning
confidence: 99%
See 3 more Smart Citations
“…The existence of the FS-decomposition has been studied by many authors, see, e.g., [17] and [18]. In particular, it was shown that the decomposition exists in the case of exponential Lévy models.…”
Section: Hedging In the Exponential Lévy Setting: The Semimartingale mentioning
confidence: 99%
“…In particular, it was shown that the decomposition exists in the case of exponential Lévy models. From the general formulas in [17] it is easy to derive that the LRM hedging number can be expressed as 12) in case the setting is observed under the historical measure P and where the prices P and the delta ∆ are determined w.r.t. the minimal martingale measure (MMM).…”
Section: Hedging In the Exponential Lévy Setting: The Semimartingale mentioning
confidence: 99%
See 2 more Smart Citations
“…Para maiores referência neste sentido, citamos os trabalhos de Pham (2000) [79], Heath et al (2001) [49] e Schweizer (2008) [90]. Mais recentemente, temos os trabalhos e Choulli et al (2010) [18] e Choulli et al (2011) [19]. Veja também o trabalho de Delong (2013) [29], em que decomposições de Föllmer-Schweizer são obtidas a partir de soluções de equações diferenciais estocásticas retrógradas (BSDEs).…”
Section: Introductionunclassified